2015
DOI: 10.1007/s13593-015-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

Salt and drought stresses in safflower: a review

Abstract: Safflower is one of the oldest cultivated crops, usually grown at a small scale. Safflower is grown for flowers used for coloring, flavoring foods, dyes, medicinal properties, and livestock feed. Safflower is underutilized but gaining attention due to oil yield potential and the ability to grow under high temperatures, drought, and salinity. Salinity and drought have negative effects by disrupting the ionic and osmotic equilibrium of the plant cells. The stress signal is perceived by membranes then transduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
135
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(138 citation statements)
references
References 191 publications
1
135
0
2
Order By: Relevance
“…The findings are in agreement with those obtained by Jabeen and Ahmad (2012) in sunflower. In particular, SOD constitutes the end product of peroxidation of membrane lipids and is the first line of defense against ROS (Hussain et al, 2016). Our result indicated that the lowest MDA content (9.13 µmol/g FW) and the highest activity (85.46 µmol min -1 mg -1 FW) of SOD were obtained from cv.…”
mentioning
confidence: 71%
“…The findings are in agreement with those obtained by Jabeen and Ahmad (2012) in sunflower. In particular, SOD constitutes the end product of peroxidation of membrane lipids and is the first line of defense against ROS (Hussain et al, 2016). Our result indicated that the lowest MDA content (9.13 µmol/g FW) and the highest activity (85.46 µmol min -1 mg -1 FW) of SOD were obtained from cv.…”
mentioning
confidence: 71%
“…Salinity stress is one of the most serious abiotic stress factors limiting crop productivity, and it is a menace for the cultivation of plants across the globe and causes drastic changes in plant growth and development (Roy et al, 2014;Hussain et al, 2016). NaClspecific damage is associated with the accumulation of Na + in leaf tissues and results in necrosis of older leaves, starting at the tips and margins and working back through the leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Under lower rainfall and limited input farming system, Safflower planting is a good choice. This plant have a great oil yield potential and able to grow under high temperatures, drought, and salinity (Hussain et al, 2015). It has also found for industrial applications such as biofuel (Dajue and Mundel, 1996).…”
Section: Introductionmentioning
confidence: 99%